Development of palm kernel oil as lubrication under extreme pressure - Misbah, Mohamad Faris (2016)
Vegetable-based lubricants are more biodegradable compared to lubricants produced from mineral oil. Due to the increasing concern about environmental damage and health caused by mineral-oil based lubricants, there is a growing worldwide trend for promoting the use of vegetable oil as lubricants in industries. Nowadays, vegetable oil is viewed as having the potential to substitute the mineral-oil based oil due to its properties such as being biodegradable and non-toxic but the problem is performance at low temperature. In this research, palm kernel oil (PKO) blended with 6 w%, 8 wt% and 10 wt% of pour point depressant (PPD) is used as lubricants to evaluate tribological behaviours using fourball tribotester. The objectives of this research are to determine the friction value and wear characteristics of PKO blended with 6 w%, 8 wt% and 10 wt% of PPD using fourball tribotester and performance of low temperature ability of lubricant. In order to determine the lubricity trait, fourball tribotester machine are used and the experiment are comply with ASTM D4172 and ASTM D2783. Parameters which covers this research are low temperature performance ability of blended PKO, coefficient of friction (COF), wear scar diameter (WSD), surface roughness and worn surface. The result of the experiment show that for low temperature performance, PKO with 10 wt% PPD (PKO-10) show great performance which can withstand 13.6℃. While for the normal load condition test, PKO – 10 performance are far better than synthetic oil (SAE15W – 50) in term of COF. However, under extreme pressure test, the blended and unblended PKO becomes unstable thus show lower performances than synthetic oil (SAE15W – 50) COF and WSD. Hence from the result, PKO – 10 have promising lubricant trait and better low temperature condition performance to be used as lubricant.